Premiers albums dans l’édition française du Second Empire - Isabelle Nières-Chevrel (Strenae)
Far from wishing to elucidate the notion of series in the field of children’s books, this contribution aims to “go back in time” and to draw up a list — possibly with commentary — of the books that two major publishers, Louis Hachette, then Pierre-Jules Hetzel and his son, undertook to publish from the Second Empire to the 1880s for the Hachette house and up to the threshold of the 20th century for those of the Hetzel house. The aim is to offer what might be called a prehistory of the series of children’s picturebooks in France.